2024
DOI: 10.1029/2023ja031403
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Mesoscale Density Structures Comprise a Significant Fraction of the Solar Wind and Are Formed at the Sun

L. Kepko,
N. M. Viall,
S. DiMatteo

Abstract: Mesoscale density structures in the solar wind are often periodic, with f ∼ 0.1–5 mHz. They are trains of advected density structures with radial length scales of ∼100–10,000 Mm. While studies have shown that these periodic density structures (PDSs) are often formed at the Sun and released into the solar wind, it is unknown what percent of the solar wind at 1 AU is comprised of PDSs from the Sun, as opposed to periodicities formed through dynamics en route. We expand on Kepko et al. (2020, https://doi.org/10.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…There is still debate on the generation mechanisms of PDSs, but there is increasing evidence toward processes involving magnetic reconnection in the solar corona (Kepko et al 2024). For example, Réville et al (2020) showed in MHD simulations that periodic variations on timescales of a few hours might result from the periodic release of flux ropes from the tip of helmet streamers via a tearing mode.…”
Section: Introductionmentioning
confidence: 99%
“…There is still debate on the generation mechanisms of PDSs, but there is increasing evidence toward processes involving magnetic reconnection in the solar corona (Kepko et al 2024). For example, Réville et al (2020) showed in MHD simulations that periodic variations on timescales of a few hours might result from the periodic release of flux ropes from the tip of helmet streamers via a tearing mode.…”
Section: Introductionmentioning
confidence: 99%